2022
DOI: 10.1002/jmv.27914
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and bioinformatics analysis for the role of antihypertension drugs on mortality among patients with hypertension hospitalized with COVID‐19

Abstract: Comorbidities such as hypertension could exacerbate symptoms of coronaviral disease 2019 (COVID)-19 infection. Patients with hypertension may receive both anti-COVID-19 and antihypertension therapies when infected with COVID-19. However, it is not clear how different classes of anti-hypertension drugs impact the outcome of COVID-19 treatment. Herein, we explore the association between the inpatient use of different classes of anti-hypertension drugs and mortality among patients with hypertension hospitalized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…47 Single-cell RNA-Seq datasets in COVID-19 patients suggested that LST1 may play a role in the effect of Angiotensin II receptor blocker on COVID-19-related mortality. 48 Therefore, LST1 not only contributes to predict the COVID-19 outcomes, but also may be a potential COVID-19 treatment target. AGER is also named RAGE, and its plasma protein level was identified to be significantly upregulated in ICU COVID-19 patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…47 Single-cell RNA-Seq datasets in COVID-19 patients suggested that LST1 may play a role in the effect of Angiotensin II receptor blocker on COVID-19-related mortality. 48 Therefore, LST1 not only contributes to predict the COVID-19 outcomes, but also may be a potential COVID-19 treatment target. AGER is also named RAGE, and its plasma protein level was identified to be significantly upregulated in ICU COVID-19 patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…New variants of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are emerging. Although the new variants of SARS‐CoV‐2 are becoming less pathogenic, 1 they appear to be transmitted more rapidly and are still capable of causing widespread epidemics 2 . Influenza viruses can also cause epidemics occasionally 3 .…”
Section: Wild Typea Group (N = 161) Mono‐infection Group Co‐infection...mentioning
confidence: 99%
“…Unduly harsh policy may cause inconvenience and huge financial burden. China has the highest proportion of older adults among the countries worldwide, and a large part of this population with underlying health conditions are more vulnerable to COVID-19 [13][14][15][16] .…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%